War of Narratives: A Concentric Dissection of China’s Taiwan Policy (Groundings Undergraduate, 2024)
This paper explores the intricate strategic narratives that China employs in its policy towards Taiwan. Through concentric analyses, it dissects China’s narratives towards Taiwan at three levels: system-level narratives, identity narratives and issue narratives. At the systemic level, China’s narrative aims to position Taiwan’s status under the broader goal of national unity and territorial integrity, emphasising the one-China policy and opposing external intervention. Identity narratives delve into shared history, culture, and nationalism to reinforce claims to Taiwan as part of China’s inherent identity and destiny. Issue narratives, on the other hand, focus on interpreting specific events, portraying reunification with Taiwan as legitimate, inevitable and a matter of national pride. This paper also mentions counter-narratives in Taiwan that emphasise Taiwan’s democratic values, unique identity and the challenges posed by China’s hard-line policies. The analysis reveals how these narratives contribute to increasing China’s international influence, undermining Taiwan’s legitimacy, and fuelling domestic nationalism, while also potentially influencing strategic responses across the region and around the world.
Keywords: Taiwan; China; Political Narratives; International Relations; Asia